An investigation into 6-S auditing in an aircraft company. (8th October 2010) - Gnanaguru, R.; Puvaneswari, K.; Mallick, Jogendra; Jegadheesan, C.; Sivakumar, V.; Devadasan, S.R.
Currently, the world is witnessing the progression of 6-S from 5-S for ensuring house keeping of organisational facilities. The success of applying 6-S would depend upon the auditing of facilities. Auditing score is often a subjective topic. The score varies depending on the auditor and his expectation. This can create much confusion when several people express their opinion on how to maintain 6S. To minimise this subjectivity, the 6-S audit worksheets were designed and developed for shop floor, stores and office. The practical validity of these 6-S audit worksheets was tested by conducting audits in an Indian public sector company by name Hindustan Aeronautics Limited.